Evaluation of a male-specific psychotherapeutic program for major depressive disorder compared to cognitive behavioral therapy and waitlist: study protocol for a six-arm randomized clinical superiority trial examining depressed eugonadal and hypogonadal men receiving testosterone - Walther, Andreas; Ehlert, Ulrike; Schneeberger, Michèle; Eggenberger, Lukas; Flückiger, Christoph; Komlenac, Nikola; Heald, Adrian; Rice, Timothy; Palm, Simona; Seidler, Zac E.; Ogrodniczuk, John S.; Oliffe, John L.; et al. (Frontiers in Psychiatry, 2023)
Background: Treatment of major depressive disorder (MDD) in men is complicated by the endorsement of traditional masculinity ideologies (TMI) often leading to reluctance towards psychotherapy, therapy interfering processes, or premature termination. In addition, it has been shown that men with MDD have a significantly increased risk of being hypogonadal (e.g. total testosterone levels < 12.1nmol/l). Therefore, it is recommended to examine depressed men with regard to their testosterone status and if hypogonadism is present to combine psychotherapy with testosterone treatment (TT). This project aims to evaluate a male-specific psychotherapeutic program (MSPP) for MDD in depressed eugonadal and hypogonadal men receiving testosterone in comparison to a standard cognitive behavioral therapy (CBT) for MDD and a Waitlist. Methods: The study presents a 2x3 factorial study design. In total, 144 men aged between 25 and 50 will be stratified by testosterone status (eugonadal / hypogonadal) and then randomized into one of the three conditions (MSPP, CBT or Waitlist). Additionally, a healthy control group of 100 men will be recruited, which will undergo only baseline assessments. Both standardized psychotherapy programs will encompass 18 sessions delivered in a weekly manner. Aligned with the TT-related medical visits of the 72 hypogonadal men, all participants will be followed up with clinical assessments and bio sampling at weeks 0, 6, 15, 24, 36. Expected results: MSPP is expected to show higher effectiveness and efficacy for depressive symptoms and higher acceptability as compared to CBT. Discussion: This study represents the first attempt to test a male-specific psychotherapy for MDD in a single-setting compared to standard CBT and a Waitlist control condition using randomized clinical trial methodology. In addition, the potential positive adjunct effect of psychotherapy to TT in reducing depressive burden and improving quality of life in hypogonadal depressed men represents a neglected research area and might introduce new hypogonadism screening procedures in depressed men and combined treatment approaches for depressed men suffering from hypogonadism. Limitations are the rigorous inclusion and exclusion criteria, which limit the generalizability of the study results to first episode treatment naïve depressed men. Trial registration: ClinicalTrials.gov, NCT05435222. Registered on 27th of June 2022.